2022
DOI: 10.1111/ddg.14696
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast in oral lichen planus – a multicentric, retrospective study

Abstract: Dear Editors, oral lichen planus (OLP) is an autoimmune-mediated inflammatory disease of the oral cavity with an estimated global prevalence of about 1.0 % [1]. Mildly affected individuals may only display the characteristic clinical features, that is, Wickham's striae of the oral mucosa, but are otherwise asymptomatic. However, certain patients may suffer from moderate to severe pain that interferes with food intake and dental hygiene [2]. Furthermore, patients with OLP are more likely to develop oral squamou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…The effective use of apremilast in erosive OLP was reported firstly only in case reports and case series ( 22 , 23 ). Furthermore, a multicentric, retrospective study on 11 OLP patients (8 of them with a coexistent cutaneous LP) was recently published ( 24 ). In this study, the authors reported that 55% of patients had an improvement of their symptoms at week 12 ( 24 ).…”
Section: Apremilastmentioning
confidence: 99%
See 2 more Smart Citations
“…The effective use of apremilast in erosive OLP was reported firstly only in case reports and case series ( 22 , 23 ). Furthermore, a multicentric, retrospective study on 11 OLP patients (8 of them with a coexistent cutaneous LP) was recently published ( 24 ). In this study, the authors reported that 55% of patients had an improvement of their symptoms at week 12 ( 24 ).…”
Section: Apremilastmentioning
confidence: 99%
“…Furthermore, a multicentric, retrospective study on 11 OLP patients (8 of them with a coexistent cutaneous LP) was recently published ( 24 ). In this study, the authors reported that 55% of patients had an improvement of their symptoms at week 12 ( 24 ). Reasons for therapy discontinuation were progression of disease in five patients (45%), adverse events in three patients (27%), and remission of disease in one (9%) patient ( 24 ).…”
Section: Apremilastmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27] A multicentre retrospective study observed clinical response in only 6 of 11 patients with oral LP after 12 weeks. 28 A case series of five patients with lichenoid and interface dermatitis observed treatment response after 12 weeks in all five patients; however, one patient had to discontinue after 11 months due to toxicity (diarrhoea and upper respiratory tract infection). Larger RCTs assessing role of apremilast in LP are lacking.…”
Section: Lichen Planusmentioning
confidence: 96%
“…A few case reports and small case series have reported favourable outcomes in mucosal LP, including erosive gingivitis and oesophageal lesions, and in patients with histological findings of lichenoid and interface dermatitis 24–27 . A multicentre retrospective study observed clinical response in only 6 of 11 patients with oral LP after 12 weeks 28 . A case series of five patients with lichenoid and interface dermatitis observed treatment response after 12 weeks in all five patients; however, one patient had to discontinue after 11 months due to toxicity (diarrhoea and upper respiratory tract infection).…”
Section: Off‐label Dermatological Uses Of Apremilastmentioning
confidence: 99%